Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Bank Central Asia KCP Cikarang - Heri Susanto; Pupung Purnamasari; Azmil Mustaqaroh (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine and prove how much influence motivation and job satisfaction have on the performance of Bank Central Asia KCP Cikarang employees. This study used a quantitative method by conducting a survey of 35 respondents to determine the effect of motivation (X1) and job satisfaction (X2) on employee performance (Y). From the results of the study it was found that the motivation, job satisfaction and performance of Bank Central Asia Cikarang Branch employees were considered good. the independent variables affect the dependent variable, where t count on motivation is 2.628 <t table 2, 034, and t count for job satisfaction is 4.186 <t table 2.034